Effect of Dilute Acid Pretreatment on the Sugarcane Leaf for Fermentable Sugars Production - Martins, Júlia Ribeiro [UNESP]; Schmatz, Alison Andrei [UNESP]; Salazar-Bryan, Ana Maria [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
Bioethanol can be produced from lignocellulosic material, however, due to the material recalcitrance, a pretreatment step is needed to improve cellulose accessibility. Dilute acid pretreatment improves the cellulose digestibility but it generates sugar and lignin degradation products. The sugarcane leaf was subjected to different operating conditions such as reaction time (10–60 min), temperature (120–80 °C), and sulfuric acid concentration (2–20%, m/m equivalent to 0.2–1.8 m/v) to evaluate the released sugars, degradation products, and pseudo-lignin formation. The conditions that resulted in higher pseudo-lignin formation were the most severe, 25.46% of pseudo-lignin. The sample with the highest pseudo-lignin formation was among those with the lowest glucose yield after the enzymatic hydrolysis, indicating that there was a pseudo-lignin inhibition. The best pretreatment conditions to maximize the enzymatic hydrolysis was 60 min of reaction at 180 °C and 2% of sulfuric acid, resulting in 94.56% of cellulose conversion into glucose.
Keywords: Bioethanol; Biomass valorization; Glucose; Pretreatment; Recalcitrance; Sugarcane straw